Dual-action kinase inhibitors influence p38α MAP kinase dephosphorylation - Emily J. Stadnicki; Hannes Ludewig; Ramasamy P. Kumar; Xicong Wang; Youwei Qiao; Dorothee Kern; Niels Bradshaw (Proceedings of the National Academy of Sciences, 2025)
Reversible protein phosphorylation directs essential cellular processes including cell division, cell growth, cell death, inflammation, and differentiation. Because protein phosphorylation drives diverse diseases, kinases and phosphatases have been targets for drug discovery, with some achieving remarkable clinical success. Most protein kinases are activated by phosphorylation of their activation loops, which shifts the conformational equilibrium of the kinase toward the active state. To turn off the kinase, protein phosphatases dephosphorylate these sites, but how the conformation of the dynamic activation loop contributes to dephosphorylation was not known. To answer this, we modulated the activation loop conformational equilibrium of human p38α ΜΑP kinase with existing kinase inhibitors that bind and stabilize specific inactive activation loop conformations. From this, we identified three inhibitors that increase the rate of dephosphorylation of the activation loop phospho-threonine by the PPM serine/threonine phosphatase WIP1. Hence, these compounds are “dual-action” inhibitors that simultaneously block the active site and promote p38α dephosphorylation. Our X-ray crystal structures of phosphorylated p38α bound to the dual-action inhibitors reveal a shared flipped conformation of the activation loop with a fully accessible phospho-threonine. In contrast, our X-ray crystal structure of phosphorylated apo human p38α reveals a different activation loop conformation with an inaccessible phospho-threonine, thereby explaining the increased rate of dephosphorylation upon inhibitor binding. These findings reveal a conformational preference of phosphatases for their targets and suggest a unique approach to achieving improved potency and specificity for therapeutic kinase inhibitors.